The Distribution of Gains from Globalization - Lang, Valentin (IMF Working Papers; Working Paper, 2018)
We study economic globalization as a multidimensional process and investigate its effect on incomes. In a panel of 147 countries during 1970-2014, we apply a new instrumental variable, exploiting globalization's geographically diffusive character, and find differential gains from globalization both across and within countries: Income gains are substantial for countries at early and medium stages of the globalization process, but the marginal returns diminish as globalization rises, eventually becoming insignificant. Within countries, these gains are concentrated at the top of national income distributions, resulting in rising inequality. We find that domestic policies can mitigate the adverse distributional effects of globalization.